2008
DOI: 10.1029/2007jg000561
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of endolithic microbial survival in the hyperarid core of the Atacama Desert by mineral deliquescence

Abstract: [1] The hyperarid core of the Atacama Desert is considered the dry limit for life on Earth. Soils in this region have very low abundance of heterotrophic bacteria and are practically barren of photosynthetic microorganisms because of the extreme dry conditions ( 2 mm a À1 rainfall). However, relatively abundant endolithic communities of cyanobacteria (Chroococcidiopsis) occur within halite crusts in paleolake evaporitic deposits. By means of continuous monitoring of the microclimate conditions (temperature, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
150
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(155 citation statements)
references
References 19 publications
5
150
0
Order By: Relevance
“…However, when the RH increased to above 70%, fluorescence appeared within minutes and stabilized at relatively low, but significantly positive, values. It is significant that activation of PSII in the halite cyanobacteria did not occur until liquid water was produced through deliquescence (8) and/or water vapor condensed within the nanopores of halite (9). Hence, it seems that photosynthesis in cyanobacteria can only be activated in the presence of liquid water (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the RH increased to above 70%, fluorescence appeared within minutes and stabilized at relatively low, but significantly positive, values. It is significant that activation of PSII in the halite cyanobacteria did not occur until liquid water was produced through deliquescence (8) and/or water vapor condensed within the nanopores of halite (9). Hence, it seems that photosynthesis in cyanobacteria can only be activated in the presence of liquid water (50).…”
Section: Discussionmentioning
confidence: 99%
“…These cells seem to be biologically adapted to conditions of high salinity, and their presence indicates a water source other than the area's practically nonexistent rainfall. Davila et al (8) showed that water vapor condenses within the halite pinnacles at relative humidity (RH) levels that correspond to the deliquescence point of NaCl (RH ϭ 75%). More recently, it was shown that halite endoliths could obtain liquid water through spontaneous capillary condensation at a relative humidity much lower than the deliquescence RH of NaCl (9).…”
mentioning
confidence: 99%
“…As mentioned above, many divalent chlorides are deliquescent, and chlorine, which is usually incorporated in solutions in the form of chlorides, is a well-known disinfectant/antiseptic. In another field, it has indeed been recently discovered that certain microorganisms are taking advantage of the deliquescent nature of some minerals present in the Atacama Desert, the driest place on Earth, to survive in such a hostile environment (5). Finally, the use of deliquescent salts to stabilize and study ultrasmall liquid droplets on solid surfaces under normal ambient conditions, which is not possible with conventional liquids such as water or organic liquids due to almost instantaneous evaporation, could provide new avenues for the study of wetting properties at ultrasmall scales, a recently reviewed hot area in surface science (19), since liquid topography can be accurately tracked at high resolution using AFM.…”
Section: Replacement Of Bacteria With Nonbiological (Almentioning
confidence: 99%
“…Halite, a palm sized piece, from the hyper-arid core of the Atacama Desert (Yungay region, Chile, donor Alfonso F. Davila, Davila et al 2008) have been employed in this study. For comparison, in particular for the hydration properties, very pure NaCl (Merck, 99.99%) and the smectite Ca-montmorillonite (STx, Gonzales County, Texas; source Clay Minerals Repository, 101 Geological Science Bldg., Columbia, MO 65211, USA) have been included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Because Wierzchos et al (2006) and Davila et al (2008Davila et al ( , 2013 showed that deliquescence of halite (sodium chloride) in the hyper-arid Atacama Desert provides a habitable environment, the Martian chloride deposits also might have an astrobiological potential . Möhlmann (2011) proposed temporary liquid cryobrines on Mars available as water source for biological processes.…”
Section: Introductionmentioning
confidence: 99%